2011
DOI: 10.3856/vol39-issue2-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Catch composition of the spiny lobster Panulirus gracilis (Decapoda: Palinuridae) off the western coast of Mexico

Abstract: ABSTRACT. The lobster fishery in the Gulf of California and the south-central region of the western coast of Mexico consists of small-scale artisanal activity supported by Panulirus gracilis and P. inflatus, with an annual average catch of 132 ton. The present study analyzes the landing composition of this fishery and the population structure of P. gracilis. Carapace lengths (CL) for this species ranged from 35 to 125 mm, and the most frequent sizes were between 60 and 85 mm. The size distribution was approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
(12 reference statements)
0
4
0
5
Order By: Relevance
“…Indeed, Aucoin & León (2007) reported the capture of three juvenile hawksbills in a 640 m lobster gillnet used in experimental bycatch trials during 24-h periods over four days in the Dominican Republic, and encountered a lobster gillnet with an additional seven dead juvenile hawksbills. In the eastern Pacific, small-scale fishers primarily use gillnets to capture lobsters (FAO, 2007;Pérez-González, 2011;Salas et al, 2011;Carrión-Cortez et al, 2013), although in Mexico, Colombia, and Ecuador lobster fishers also employ traps and diving (Beltrán, 2005;Salas et al, 2011). We expect hawksbill bycatch to be greatest in lobster gillnet fisheries along the coast of Central America, where intense use of lobster gillnets occurs in areas relatively adjacent to major nesting grounds for this species in the region (Gaos et al, 2017), which employs short migrations between nesting and foraging areas (Gaos et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Aucoin & León (2007) reported the capture of three juvenile hawksbills in a 640 m lobster gillnet used in experimental bycatch trials during 24-h periods over four days in the Dominican Republic, and encountered a lobster gillnet with an additional seven dead juvenile hawksbills. In the eastern Pacific, small-scale fishers primarily use gillnets to capture lobsters (FAO, 2007;Pérez-González, 2011;Salas et al, 2011;Carrión-Cortez et al, 2013), although in Mexico, Colombia, and Ecuador lobster fishers also employ traps and diving (Beltrán, 2005;Salas et al, 2011). We expect hawksbill bycatch to be greatest in lobster gillnet fisheries along the coast of Central America, where intense use of lobster gillnets occurs in areas relatively adjacent to major nesting grounds for this species in the region (Gaos et al, 2017), which employs short migrations between nesting and foraging areas (Gaos et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pelagic longlines used by industrial fleets are a primary source of mortality for older, reproductively valuable leatherback turtles (Dermochelys coriacea) in the Pacific Ocean (Lewison et al, 2004;Donoso & Dutton, 2010), where fewer than 3,000 adult females nest in the entire oceanic basin (Benson et al, 2015). However, smallscale, artisanal fisheries also are coming under increasing scrutiny as important sources of bycatch across taxa commensurate with or surpassing levels found in large-scale fisheries (Zydelis et al, 2009;Alfaro-Shigueto et al, 2010b, 2011Gilman et al, 2010;Peckham et al, 2016). Mangel et al (2010), for instance, reported cetacean bycatch-per-unit-effort (BPUE) in Peruvian artisanal drift gillnet fisheries to be comparable to BPUE for the large-scale Moroccan driftnet fleet in the southwest Mediterranean.…”
Section: Introductionmentioning
confidence: 99%
“…Panulirus gracilis occupies different types of benthic habitats, from rocky bottoms with clear water to gravel-sand bottoms near river discharges where water can be considerably turbid, whereas Panulirus inflatus occurs exclusively in rocky habitats with clear waters (Briones et al 1981, Pérez-González et al 1992, Pérez-González 2011). Although these findings suggest that Panulirus inflatus might be considered a habitat specialist and Panulirus gracilis a habitat generalist, an important criterion to consider a benthic species as habitat specialist is that its postlarvae settle into the same type of habitat where the adults live, and as habitat generalist that the postlarvae are able to settle in various types of habitats (Adams et al 2006, Adams and Ebersole 2009); however, the natural settlement habitats have not been determined for either Panulirus inflatus or Panulirus gracilis .…”
Section: Eastern Central Pacific: Panulirus Gracilis and Panulirus Inmentioning
confidence: 99%
“…Vega, Robles y Gil (76.68 mm, calculada a partir de promedios mensuales entre 1989 y 1990) y el Pacífico de Costa Rica (72.5 mm) (Arzola-González et al 2011;Pérez-González, 2011;Naranjo-Madrigal, 2011). Probablemente, el hecho de que las langostas en el Golfo de Montijo sean más grandes está relacionado con una menor presión pesquera comparada con las restantes localidades, e inclusive en el propio Pacífico panameño, donde tallas promedios de captura de 67 mm de LC fueron reportadas por Guzmán et al (2008) para el Archipiélago de las Perlas, Pacífico Oriental de Panamá, donde la actividad extractiva de langosta es más intensa comparada con el Golfo de Montijo, en el que los principales recursos pesqueros son los peces y los camarones penaeidos.…”
Section: Cpue Añosunclassified